Use of a novel drainage flow servo-controlled CPB for mitral valve replacement in a Jehovah's Witness. (September 2018) - Niimi, Yoshinari; Murata, Seiichiro; Mitou, Yumi; Ohno, Yusuke
We developed a novel open cardiopulmonary bypass (CPB) system, a drainage flow servo-controlled CPB system (DS-CPB), in which rotational speed of the main roller pump is servo-controlled to generate the same amount of flow as the systemic venous drainage. It was designed to safely decrease the priming volume while maintaining a constant reservoir level, even during fluctuations of the drainage flow. We report a successful use of a novel DS-CPB system in an elderly Jehovah's Witness patient with dehydration who underwent mitral valve replacement.